Quasi-LPV modelling of a projectile's behaviour in flight. Issue 15 (2018) - Machala, Dawid; Dobre, Simona; Albisser, Marie; Collin, Floriane; Gilson, Marion
Abstract: The behaviour of a projectile in flight is usually described by the Newton-Euler equations of motion, through a nonlinear model structure. Its transformation into a quasi-LPV form often requires the model to be simplified, or analysed only as a set of locally linearized approximations of the system. Consequently, the region of validity of the model is reduced. In this paper, the aim is to develop a less restrictive modelling approach, based on two main steps. Firstly, the nonlinear model is described w.r.t. a so-called non-rolling reference frame, which allows to reduce the model complexity while preserving its accuracy. Then, a quasi-LPV model is developed using an analytical function substitution method, where the scheduling variables correspond to the values which are measurable or observable during real-world experiments. Consequently, a model whose validity is not restricted to an equilibrium manifold is created. The validation of the quasi-LPV model developed in a non-rolling frame, w.r.t. the nonlinear one developed in a standard rolling frame, is performed through a series of simulations.